Survival in patients with COVID-19 admitted to ICU in a third-level hospital in Lambayeque, Peru. - Aguirre-Milachay, Edwin (2023)
Introduction: COVID-19, caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), has reached pandemic proportions worldwide, persisting over time. In this context, this study aims to analyze the factors associated with mortality in hospitalized patients with COVID-19 in a third-level hospital in the Lambayeque region. Material and metodo: A retrospective cohort study was conducted on patients diagnosed with COVID-19, hospitalized at the National Hospital Almanzor Aguinaga Asenjo (HNAAA) during the months of March to September 2020. Results: Forty patients admitted to the Intensive Care Unit (ICU) were examined, of whom twenty-two required mechanical ventilation (MV). Overall mortality in the ICU was 68.7%, while mortality among patients who required mechanical ventilation was 91.6%. A statistical association was found between death and vital signs on admission to the ICU, as well as with the waiting time for admission. The probability of survival at 2 and 7 days was 90.1% and 45.5%, respectively. Conclusions: In this cohort, a mortality rate of 68.7% was observed in the ICU, with a survival rate of 45.5% at 7 days and less than 10% at 18 days. No associations were found between survival and any of the variables of interest.